Selected Papers from the 5th International Symposium on Mycotoxins and Toxigenic Moulds: Challenges and Perspectives - Siska Croubels (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
The MYTOX association research platform, MYTOX "Mycotoxins and Toxigenic Moulds" was established in 2007 and consists of more than 50 researchers from 12 research laboratories in the Ghent University Association. MYTOX deals with mycotoxin research in a multi-disciplinary way, based on four main themes: (1) mycotoxins; (2) toxigenic fungi; (3) mycotoxins and animal health; and (4) mycotoxins and human health. In this way, MYTOX tackles the mycotoxin issue along the production chain from the field to the end consumer, within the 'One Health' concept. We welcomed over 100 scientists, researchers and representatives from industry, government as well as academia at the 5th edition of the MYTOX International Symposium, held in Ghent on May 11, 2016. The program included oral and poster presentations related to fungal-related disease monitoring and mycotoxin production; mycotoxin analysis in food and feed, as well as in animal and human biological samples; prevention on the field; management strategies during food and feed storage and processing.